Shadow Toolbox (1st release) - Allahvirdizadeh, Amir (GitHub - figShare, 2022)
Shadow is a Matlab toolbox written to detect the GNSS satellite in the shadow of the earth and remove them from the RINEX observation file. The main toolbox performs the following tasks: 1- Reads Rinex observation file 2- Reads precise ephemeris file (SP3) 3- Detect the satellite in the shadow of the Earth 4- Remove the observation of the satellite and create a refined Rinex